11 Pennsylvania Statutes at Large ch. 1059 at 209-12 (1906) - (:unkn) unknown (My University, 1782)
prohibited storing more than 30 pounds of gunpowder in Philadelphia or within two miles, except in the public powder magazine
Keywords: GUNPOWDER STORAGE